2008
DOI: 10.1177/089686080802802s03
|View full text |Cite
|
Sign up to set email alerts
|

Renal Osteodystrophy in Peritoneal Dialysis: Special Considerations

Abstract: Bone disease is one of the most challenging complications in patients with chronic kidney disease. Today, it is considered to be part of a complex systemic disorder manifested by disturbances of mineral metabolism and vascular calcifications called chronic kidney disease – mineral bone disorder (CKD-MBD). The term renal osteodystrophy is reserved to define the specific bone lesion in CKD-MBD, whose spectrum ranges from high turnover to low turnover disease. Phosphate retention, decreased serum calcium, and 1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 73 publications
2
2
0
1
Order By: Relevance
“… 17 Our data showed that the relationship between BCL and low turnover bone disease persisted even after adjusting for factors previously described as confounders. 34 These data were in agreement with a previous study which showed a significant inverse association between serum PTH and BCLs. 35 The mechanism underlying this association is thought to be mediated by increased osteoclast bone resorption, which mobilizes more calcium from skeletal to the circulation.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“… 17 Our data showed that the relationship between BCL and low turnover bone disease persisted even after adjusting for factors previously described as confounders. 34 These data were in agreement with a previous study which showed a significant inverse association between serum PTH and BCLs. 35 The mechanism underlying this association is thought to be mediated by increased osteoclast bone resorption, which mobilizes more calcium from skeletal to the circulation.…”
Section: Discussionsupporting
confidence: 93%
“… 3 Critically, accumulating evidence indicated that either low turnover bone disease or higher calcium load to the circulation may contribute substantially to increased death risk in dialysis patients. 34 , 36 Moreover, low turnover bone disease in dialysis patients has been implied to be a consequence of the malnutrition–inflammation complex syndrome, 37 providing further support to our first hypothesis.…”
Section: Discussionsupporting
confidence: 71%
“…Patients on PD may have different mineral metabolism disorders than patients on hemodialysis, including a higher frequency of adynamic bone disease (4) or a reduced risk of cardiac valve calcification over time, probably related to the higher prevalence of residual renal function (RRF) (5). Observational studies of small numbers of patients on PD have described a prevalence of vascular calcification in the range of 32 -60% (6)(7)(8).…”
mentioning
confidence: 99%
“…En ce qui concerne le magnésium, une concentration dans le dialysat de 0,25 mmol/l conduit à une extraction péritonéale de l'ordre de 0,5 à 1 mmol/l, soit une valeur également proche de l'élimination urinaire quotidienne. L'ostéodystrophie rénale du patient en DP est marquée par une très forte prévalence de l'ostéopathie adynamique (près de 50%) (tableau II) (15). La prévention de cette complication nécessite d'éviter le recours aux solutions de dialyse à concentration élevée de calcium (> 1,25 mmol/l), et de limiter l'apport oral de calcium à moins de 1,5 g/jour de calcium-élément.…”
Section: Concentration De Calcium Et Magnesiumunclassified